Peran Pemberdayaan Komunitas dalam Mendorong Efektivitas Program Pengawasan Partisipatif Pemilu oleh Bawaslu Provinsi Jawa Timur - NataliaNatalia, Margareta Dea (TSAQOFAH, 2026)
This study examines the role of community empowerment in enhancing the effectiveness of participatory election monitoring programs implemented by Bawaslu of East Java Province. Although participatory monitoring programs have been widely introduced, research that specifically highlights the contribution of communities as strategic monitoring partners remains limited. This study aims to analyze how community empowerment contributes to improving election literacy, expanding monitoring networks, and strengthening active public participation in election oversight. Using a qualitative approach with a case study design, data were obtained through interviews with staff of the Divisi Parmas and analysis of records from participatory monitoring education activities. The findings show that community empowerment can improve public understanding of electoral processes and regulations, broaden monitoring networks at the grassroots level, and encourage citizens’ involvement in reporting potential violations. Nevertheless, program effectiveness is still constrained by limited community capacity, the continuity of mentoring, and suboptimal program follow-up. These findings affirm that community strengthening is a key strategy for optimizing election monitoring based on public participation and provide practical implications for Bawaslu to design empowerment schemes that are more structured, sustainable, and responsive to the needs of partner communities.